Comparison of CONUT Score, SGA Score, and GLIM Score as Gold Standard for Colorectal Cancer Patients - Marcella, Marcella; Rudiman, Reno; Yohana, Raden (Faculty of Medicine, Universitas Padjadjaran, 2025)
Malnutrition in colorectal cancer increases toxicity, worsens quality of life, and reduces body functions. Early identification of malnutrition is crucial to determine treatments. This study compared the Global Leadership Initiative on Malnutrition (GLIM) score as the standard nutritional status screening tool to the Controlling Nutritional Status (CONUT) and Subjective Global Assessment (SGA) scores. This study expected to identify a new nutritional status screening tool for colorectal cancer patients. This was a cross-sectional diagnostic study on 60 colorectal cancer patients treated at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia from August 16, 2022 to July 16, 2023. Results revealed that the CONUT score had a sensitivity, specificity, accuracy, and effectiveness values of 80.4%, 0.0%, 85%, and 85%, respectively, in detecting malnutrition. The SGA score had a sensitivity value of 100%, a specificity value of 21.95%, an accuracy value of 85%, and an effectiveness of 85% in detecting malnutrition. When compared with the GLIM score as the gold standard, which is assumed to have a sensitivity and specificity values of 100%, the SGA score was better than the CONUT score for detecting malnutrition in colorectal cancer patients. The SGA score is closest to the GLIM score as the gold standard for assessing malnutrition in colorectal cancer patients.